2021
DOI: 10.1111/ajr.12745
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Allied Health Rural Generalist Program 2017‐2019

Abstract: Objective: To evaluate the development and implementation of the Allied Health Rural Generalist Program, a two-level online post-graduate education program, which includes Level 1, an entry-level non-award pathway program, and Level 2, a Graduate Diploma in Rural Generalist Practice. Design: A convergent mixed methodology evaluation in two overlapping stages: a process evaluation on quality and reach, together with a mixed method case study evaluation on benefits, of the program. Setting: Rural and remote Aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 31 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…A review by Roots and Li [ 62 ] also found career advancement limitations in rural areas for occupational therapists and physiotherapist was a challenge that negatively impacted job satisfaction and retention. A rural generalist pathway for early career allied health professionals was introduced in Australia 2014 [ 63 ] in an attempt to give early career clinicians the opportunity to develop specialised rural practice skills, leadership and service development skills. At the time of this review, the rural generalist pathway does not appear to lead to a recognised career path or endorsement of specialty status.…”
Section: Discussionmentioning
confidence: 99%
“…A review by Roots and Li [ 62 ] also found career advancement limitations in rural areas for occupational therapists and physiotherapist was a challenge that negatively impacted job satisfaction and retention. A rural generalist pathway for early career allied health professionals was introduced in Australia 2014 [ 63 ] in an attempt to give early career clinicians the opportunity to develop specialised rural practice skills, leadership and service development skills. At the time of this review, the rural generalist pathway does not appear to lead to a recognised career path or endorsement of specialty status.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐urban contexts, while non‐homogenous and unique (Moran et al, 2021 ), are typified by small populations, separated by geographic distances, with limited access to infrastructure (Carson et al, 2011 ; Farias & Faleiro, 2021 ), thus, identifying sufficient population to provide a stratified service that may be fraught and contrasts with consistent non‐urban therapist reports citing the requirement of both generalist knowledge and practice approach (e.g. Barker et al, 2021 ; Orda et al, 2017 ; Roots et al, 2014 ; Woolley et al, 2019 ). Some of this contextual misunderstanding may result from the significant number of publications found reporting on services provided by occupational therapists not living in the non‐urban community they served, with many originating from urban spaces.…”
Section: Discussionmentioning
confidence: 99%
“…The development of specialties with associated career paths was not a focus of allied health papers, some ndings centred on opportunities for leadership in rural areas early in their career, while others reported the opposite with a lack of senior roles impacting on career advancement. A rural generalist pathway for early career allied health professionals was introduced in Australia 2014 (55) in an attempt to give early career clinicians the opportunity to develop specialised rural practice skills, leadership and service development skills. At the time of this review, the rural generalist pathway does not appear to lead to a recognised career path or endorsement of specialty status.…”
Section: Discussionmentioning
confidence: 99%